PERKEMBANGAN DAN PROSPER BISNIS JAWA TIMUR - Zafrullah, Ahmad (Journal of Management and Business, 2002)
Superiority export commodity of East Java to Japan, USA, China, Australia, South of Korea, Taiwan and other countries are textile, pulp, garment, plywood, tobacco, coffee, tea and shrimp.The research aims to analyze the development of industrial and agriculture products in East Java. The descriptive and comparative analysing secondary data result that East Java economic conjunctur influenced by three main sectors, that is; (a) agriculture (b) industrial manufacture (c) trade, hotel and restaurant that consistently to keep significant supporting to GRDP of East Java.The effort of government to deal with the trade problems, that is, to enlarge foreign market, business information, to anticipate global liberalization, and international cooperation.